Community patterns and environmental drivers in hyper‐diverse kwongan scrub vegetation of Western Australia. Issue 4 (13th November 2018) - Tsakalos, James L.; Renton, Michael; Dobrowolski, Mark P.; Feoli, Enrico; Macintyre, Paul D.; Veneklaas, Erik J.; Mucina, Ladislav
Abstract: Questions: The community patterns in kwongan, a mediterranean‐type scrub on nutrient‐poor soils occurring in Western Australia, are poorly understood due to only few, focused studies using disparate sampling designs. We aimed to determine whether (a) classification of the kwongan vegetation of the Eneabba Sandplains leads to an ecologically informative classification scheme, and (b) we could identify environmental drivers underpinning the plant community patterns. Location: Township of Eneabba (29°82′S, 115°27′E), approximately 250 km north of Perth, Western Australia, covering 1, 210 km 2. Methods: We used a data set consisting of 512 relevés, collected following the standard field methodology of the Braun‐Blanquet approach, and accompanied by an extensive set of environmental data consisting of 94 variables representing climate, fire, soil and terrain properties across 189 relevés. The data were classified and ordinated by a series of multivariate analyses. OptimClass assisted in the selection of the most robust classification procedure. Distance‐based redundancy analysis (db‐RDA) inferred the major ecological drivers of the vegetation patterns. Results: Numerical classification, nonmetric multidimensional scaling, and syntaxonomic tabular analysis revealed two major community groups (MCG A and B), eight community groups, and 17 communities in the kwongan vegetation of the study area. All vegetation units are characterised in terms of floristic composition and position along major ecological gradients in the studied area. The MCGs separated along a composite gradient of soil‐texture and exchangeable cations. The first two db‐RDA axes explained 21% of the total variance which is very low, considering the high number of environmental variables used. Conclusions: Our study provides a comprehensive insight into the high variability of vegetation types in hyper‐diverse kwongan scrub at a landscape spatial scale; it is the first syntaxonomic account of the Western Australian kwongan vegetation, presenting a complete tabular comparative analysis. The studied major community groups segregate along a soil‐texture and an exchangeable‐cation content gradient. At a community scale, environmental filtering explained a small fraction of the vegetation–environment relationship. We suggest that the unexplained portion of the vegetation‐environment relationship might be a product of slow‐acting neutral processes in this hyper‐diverse system; this assertion is amenable to rigorous future testing. Abstract : We provide the first syntaxonomic account of the community patterns in the hyper‐diverse kwongan scrub occurring on nutrient‐poor soils of Eneabba, Western Australia. A comprehensive set of environmental variables explained a small proportion of the vegetation–environment relationship. We suggest that the large unexplained proportion of the vegetation–environment relationship might be a product of long‐term, slow‐acting neutral processes.